Reapprendre à voir: Images, Symptoms and the Media of Appearance. - Vachninas, Benediktas (Problems / Problemos, 2023)
The article "Reapprendre à voir: Images, Symptoms and the Media of Appearance" features an interview with Emmanuel Alloa, a Professor of Aesthetics and Philosophy of Art, discussing his concept of symptomatology of images. Alloa emphasizes the importance of understanding images in their variety and complexity, rejecting rigid definitions in favor of a phenomenological approach. He explores the role of symptoms in identifying common features of images and engages in a dialogue between phenomenology and visual semiotics. Alloa also delves into the relationship between images, symptoms, and the power dynamics embedded in visual culture, suggesting that a deeper understanding of images can lead to critical insights and new trajectories in philosophy.